Preparation, characterization, and antiproliferative activities of biotin-decorated docetaxel-loaded bovine serum albumin nanoparticles - Kai Cheng; Shaoping Sun; Xianfeng Gong (Universidade de São Paulo, 2018)
ABSTRACT The aim of the present study was to characterize biotin-decorated docetaxel-loaded bovine serum albumin nanoparticles (DTX-BIO-BSA-NPs) and evaluate their antiproliferative activity in vitro. The particle size of prepared DTX-BIO-BSA-NPs was found to be always lower than 200 nm, with sizes of 166.9, 160.3, 159.0, 176.1 and 184.8 nm and the zeta potential was -29.51, -28.54, -36.54, -36.08 and -27.56 mV after redissolution with water for 0, 1, 2, 4 and 8 hours, respectively. The polydispersity index (PDI) was stable in the range of 0.170 - 0.178. In the in vitro drug-release study, the DTX-BIO-BSA-NPs targeted a human breast cancer cell line MCF-7 effectively. The x-ray diffraction spectrum and DSC curve of DTX-BIO-BSA-NPs suggested that docetaxel was in an amorphous or disordered crystalline phase in DTX-BIO-BSA-NPs. In vitro cytotoxicity results showed that DTX-BIO-BSA-NPs inhibits proliferation of MCF-7, SGC7901, LS-174T and A549 cells in a concentration-dependent manner after exposure to DTX-BIO-BSA-NPs for 48 hours. Taken together, these results indicate that DTX-BIO-BSA-NPs may have potential as an alternative delivery system for parenteral administration of docetaxel.